Clinical Predictors for Neutrophil-to-Lymphocyte Ratio Changes in Patients with Chronic Hepatitis B Receiving Peginterferon Treatment - LE, PUO-HSIEN (In Vivo, 2017)
Background: A lower neutrophil–to–lymphocyte ratio (NLR) was found to be associated with better clinical outcomes in hepatitis B-related liver cirrhosis and hepatocellular carcinoma. We aimed to identify pre-therapeutic variables capable of predicting NLR changes in patients with hepatitis B receiving peginterferon therapy. Patients and Methods: The baseline clinicopathological data were analyzed to correlate with NLR changes before and 1 year after peginterferon treatment in 71 patients with hepatitis B. Results: Univariate analysis revealed that pre-treatment NLR itself negatively predicted NLR changes following peginterferon treatment (odds ratio(OR)=0.320, p=0.013). Further analysis identified pre-treatment NLR, hemoglobin and hepatitis B surface antigen level as independent predictors for NLR changes (adjusted p=0.028, 0.005, and 0.028, respectively). A predictive score composed of these three factors had an area under the curve of 76.5% (p<0.001). Conclusion: Pretreatment NLR, hemoglobin and hepatitis B surface antigen level in combination, effectively predicted NLR changes following peginterferon treatment.